Relationships Between Employment and Crime: A Survey of Brooklyn Residents, 1979-1980 - Thompson, James W. ([Verlag nicht ermittelbar], 1987)
The study was designed to explore the relationship between employment and involvement with the criminal justice system. Males arrested primarily for felony offenses were interviewed at the central booking agency in Brooklyn, New York, at the time of their arrests in 1979. A subsample of 152 arrestees was reinterviewed in 1980. The data include information on labor market participation, arrests, periods of incarceration, and the respondents' demographic characteristics. The labor market information spans a two-year period prior to those arrests. Arrest history and other criminal justice data cover the two years prior to arrest and one year following the arrest. Additional variables supply information on employment and occupation, social and neighborhood characteristics, and perceptions of the risk of committing selected crimes.